Benthic hydroids (Cnidaria, Hydrozoa) from bathyal and abyssal depths of the Northeast Atlantic held in the modern Discovery Collections - Cantero, Álvaro L. Peña; Horton, Tammy (Zootaxa, 2017)
The deep-sea benthic hydroid fauna remains poorly known, in part because of less frequent sampling than the shelf fauna, in part owing to the immense study area, and partly also because available samples have been little studied by experts. In order to correct this, deep-sea benthic hydroid material from the modern Discovery Collections has been studied. Samples come from localities in the North-East Atlantic including the Porcupine Seabight, Porcupine Abyssal Plain, Rockall Trough, Rockall Bank, and the Mid-Atlantic Ridge. Sixteen species belonging to 12 families and 16 genera were found. Leptothecata are clearly dominant, being represented by 14 species; the remaining species belong to Anthoathecata. Lafoeidae and Tiarannidae are the most diverse families with three species each; the remaining families being represented by a single species. The low species diversity is remarkable at the generic level, with each genus being represented by a single species. Hydroid occurrence is low: twelve species were found in ≤ 9% of stations; Amphinema biscayana has the highest occurrence (27% of stations). Fifteen species were recorded in the Porcupine Seabight, two in the Rockall Trough, one at Rockall Bank, one on the Porcupine Abyssal Plain, and two at the Mid-Atlantic Ridge. The known bathymetric range for a third of the species is extended; the increase is particularly noteworthy in Amphinema biscayana, Acryptolaria crassicaulis, Clytia gigantea and Schizotricha profunda. Two distinct bathymetric groups are recognized: strictly deep-sea inhabitants and eurybathic species. Most species are globally distributed, some are widely distributed in the Atlantic, and others are limited to the North Atlantic or the Northeast Atlantic.